Occupying Wall Street : the inside story of an action that changed America (OR Books, 2011)
Publisher's description: "For two months this fall, Zuccotti Park, squeezed deep in a canyon between bankers' skyscrapers in lower Manhattan, was the site of an extraordinary political action. Home to the hundreds of anti-capitalist protestors who camped there overnight, and the thousands who visited to join the protest, the park became a magical place: a communion of sharing and consensus in the heart of a citadel defined by greed and oligarchy ... Now, in a new book assembled by a group of writers active in support of the occupation, the story of Occupy Wall Street is being told. Occupying Wall Street draws on extensive interviews with those who took part in the action to bring an authentic, inside-the-square history to life. In these pages you will discover in rich detail how the protest was devised and planned, how its daily needs were met, and how it won overwhelming support across the nation."